Non-muscle Myosin-II Is Required for the Generation of a Constriction Site for Subsequent Abscission - Wang, Kangji; Wloka, Carsten; Bi, Erfei (iScience, 2019)
It remains unknown when, where, and how the site of abscission is generated during cytokinesis. Here, we show that the sites of constriction, i.e., the sites of future abscission, are initially formed at the ends of the intercellular bridge during early midbody stage, and that these sites are associated with the non-muscle myosin-IIB (not myosin-IIA), actin filaments, and septin 9 until abscission. The ESCRT-III component CHMP4B localizes to the midbody and “spreads” to the site of abscission only during late midbody stage. Strikingly, inhibition of myosin-II motor activity by a low dose of Blebbistatin completely abolishes the formation of the constriction sites, resulting in the localization of all the above-mentioned components to the midbody region. These data strongly suggest that a secondary actomyosin ring provides the primary driving force for the thinning of the intercellular bridge to allow ESCRT-mediated membrane fission. [Display omitted] •Myosin-II motor activity is required for the generation of an abscission site•Myosin-II, F-actin, and septin 9 are associated with the site of abscission•ESCRT-III cannot generate an abscission site independently of myosin-II motor activity•Different myosin-II isoforms display distinct localization patterns during abscission Cell Biology; Functional Aspects of Cell Biology; Molecular Biology